Left subdiaphragmatic paraganglioma supplied by contralateral right renal artery - Martinez, Jaime D. (Elsevier, 2012)
INTRODUCTION: Paragangliomas are neuroendocrine tumors of the autonomic nervous system that arise from neural crest cells. Paragangliomas are typically extra-adrenal, non-functional and can be discovered incidentally, posing diagnostic and therapeutic challenges. PRESENTATION OF CASE: We present the unusual case of a young man who presented with an acute abdomen secondary to small bowel obstruction, and was found to have an incidental left-sided subdiaphragmatic paraganglioma supplied by a branch of the contralateral right renal artery. DISCUSSION: Emergent laparotomy revealed an internal hernia as the source of the small bowel obstruction. Initial attempts to remove an incidental left subdiaphragmatic mass were aborted because of bleeding. Subsequently, after preoperative superselective embolization of the feeding vessel arising from the right renal artery, the mass was successfully resected. Pathology was consistent with a paraganglioma. CONCLUSION: This report highlights the rarity of the location and blood supply of an incidental left subdiaphragmatic paraganglioma found in the setting of a small bowel obstruction.